Problematika Perkuliahan Analisis Real : Systematic Literature Review - Milda Zohra; Rusi Ulfa Hasanah; Annisa Putri Lubis (Jurnal Mahasiswa Kreatif, 2024)
This research aims to analyze meta data related to real analysis lecture problems. This research uses the SLR (Systematic Literature Review) method. This systematic review identified 7 articles through the Google Scholar database published in 2019-2024. Data collection used the PRISMA procedure. The results of this research show that there are 3 research objectives related to the problems of real analysis lectures, namely: 1) to find out what factors influence students' learning difficulties during real analysis courses, 2) to find out students' reasoning abilities in real analysis courses, 3) to find out how much students know about the connection between real analysis and school mathematics.